Legal Translaboration for Effective Intercultural Communication - Adrien Bell (Editura Universității „Alexandru Ioan Cuza” din Iași, 2021)
The European-inspired bilingualism and bi-legal system in Cameroon lead to an irregular profile and may be interesting for the European Union (EU) in its quest for preservation of intercultural processes through translation. The Organization for the Harmonization of Business Law in Africa (OHADA) of which Cameroon is part is only affiliated to Civil Law. However, the two legal systems employed in Cameroon (where both Civil Law and Common Law are used) are based on a balance in what concerns the conceptual, epistemic and stylistic representation. Intercultural dysfunction is the consequence of the lack of methodology in legal translation. Collaboration between legal translators and practitioners is key to adopt an agreed-upon model in multilingualism.